A study on the grief process of bereaved family members of terminally ill patients of selected municipalities in Region 8. - Bornillo, Vic Marie L., et al; Gerale, Ian Earl Shieldon L.; Villafranca, Ruby Anne G. (Vic Marie L. Bornillo, Ian Earl Shieldon L. Gerale [and] Ruby Anne G. Villafranca, 2010)
This is a descriptive study which aims to understand the self-evaluation of 16 bereaved family members of selected municipalities in Region 8 whose loved ones died because of terminal illness. Besides, it also shows how these families coped with and took actions with regards to the patients' health conditions.